Staying and studying: narratives of local higher education in small island colleges. Issue 7 (10th November 2022) - Henderson, Holly
ABSTRACT: Due to the unequal geographical distribution of HE institutions in many national HE systems, living in a rural or remote area and attending HE can be mutually exclusive. The implication is that those who remain in a rural area beyond school age do not study at the undergraduate level. In discussions of rural stayers, HE is therefore understood as a crucial point of transition between staying and leaving; HE requires or offers the opportunity to move from a rural or remote location in order to continue education. This article asks how the figure of the rural and remote stayer is changed by the relatively recent provision of HE opportunities in some rural and remote contexts in and around the UK, making it possible both to 'stay' and to study for an undergraduate degree. The article brings together literature on HE mobilities and on remote and rural staying to develop the new figure of the 'stayer-student', using a spatial narrative framework to analyse findings from a multi-sited case study of HE providers on small islands with relationships to the UK. The analysis identifies three types of spatial story that articulate the boundaries of students' remote location and HE. In the first of these stories, the boundary around the island is solidified by the decision to stay for HE, reinforcing belonging to and possibilities within place. The second focuses on the role of the spatial boundary in distinguishing between common definitions of the role and purpose of HE. In the final story, the boundary enables the disruption of linear and normative HE trajectories. Each of these findings challenges traditional understandings of the role of HE in prompting social and geographical transition away from remote and rural areas.